Antifungal features and properties of chitosan/sandalwood oil Pickering emulsion coating stabilized by appropriate cellulose nanofiber dosage for fresh fruit application - Ata Aditya Wardana (Nature Portfolio, 2021)
Abstract A novel composite edible coating film was developed from 0.8% chitosan (CS) and 0.5% sandalwood oil (SEO). Cellulose nanofibers (CNFs) were used as a stabilizer agent of oil-in-water Pickering emulsion. We found four typical groups of CNF level-dependent emulsion stabilization, including (1) unstable emulsion in the absence of CNFs; (2) unstable emulsion (0.006–0.21% CNFs); (3) stable emulsion (0.24–0.31% CNFs); and (4) regular emulsion with the addition of surfactant. Confocal laser scanning microscopy was performed to reveal the characteristics of droplet diameter and morphology. Antifungal tests against Botrytis cinerea and Penicillium digitatum, between emulsion coating stabilized with CNFs (CS-SEOpick) and CS or CS-SEO was tested. The effective concentration of CNFs (0.24%) may improve the performance of CS coating and maintain CS-SEO antifungal activity synergistically confirmed with a series of assays (in vitro, in vivo, and membrane integrity changes). The incorporation of CNFs contributed to improve the functional properties of CS and SEO-loaded CS including light transmission at UV and visible light wavelengths and tensile strength. Atomic force microscopy and scanning electron microscopy were employed to characterize the biocompatibility of each coating film formulation. Emulsion-CNF stabilized coating may have potential applications for active coating for fresh fruit commodities.